Strange harvest : organ transplants, denatured bodies, and the transformed self - Sharp, Lesley Alexandra (University of California Press, 2006)
Strange Harvest illuminates the wondrous yet disquieting medical realm of organ transplantation by drawing on the voices of those most deeply involved: transplant recipients, clinical specialists, and the surviving kin of deceased organ donors. In this rich and deeply engaging ethnographic study, anthropologist Lesley Sharp explores how these parties think about death, loss, and mourning, especially in light of medical taboos surrounding donor anonymity. As Sharp argues, new forms of embodied intimacy arise in response, and the riveting insights gleaned from her interviews, observations, and d.